Calculating potential growth rates and output gaps : a revised production function approach - Denis, Cecile; Grenouilleau, Daniel; McMorrow, Kieran; Roger, Werner; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
Any meaningful analysis of cyclical developments, of medium term growth prospects or of the stance of fiscal and monetary policies are all predicated on either an implicit or explicit assumption concerning the rate of potential output growth. Given the importance of the concept, the measurement of potential output is the subject of contentious and sustained research interest. All the available methods have "pros" and "cons" and none can unequivocally be declared better than the alternatives in all cases. Thus, what matters is to have a method adapted to the problem under analysis, with well defined limits and, in international comparisons, one that deals identically with all countries. This is the approach adopted in the present paper where it is stated clearly that the objective is to produce an economics based, production function, method which can be used for operational EU policy surveillance purposes.
Economic Papers